Сутність управлінської компетентності майбутніх офіцерів - Пономаренко, Павло (Національний технічний університет "Харківський політехнічний інститут", 2023)
Розглянуто роль рівню управлінської компетентності офіцерів ЗС України в сучасних умовах повномасштабної російської агресії проти України. У роботі на основі теоретичного аналізу сутності поняття “управлінська компетентність майбутнього офіцера” уточнено його зміст. Цю компетентність визначено як інтегровану складову професійної компетентності, яка обумовлює його здатність до ефективної військово-управлінської діяльності у мирний та воєнний час на основі здобутих знань, умінь, навичок та особистісно-професійних якостей.

In today’s conditions of full-scale Russian aggression against Ukraine, the managerial competence level of the Armed Forces of Ukraine officers becomes especially important. The definition of the “management competence of the future officer” essence remains insufficiently researched. The article based on the conducted theoretical analysis clarifies the essence of the managerial competence concept of the future officer as an integrated component of professional competence, which determines his ability to perform effective military management activities in peacetime and wartime on the basis of acquired knowledge, abilities, skills, personal and professional qualities.
The essence of management competence of future officers
Keywords: компетентність; управлінська компетентність; військово- професійна діяльність; майбутні офіцери; competence; management competence; military professional activity; future officers